Penyelesaian Sengketa Tanah Kehutanan di Kantor Pertanahan Kabupaten Badung - I Gede Edy Korneawan; A.A Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2020)
Land is one of the most important parts of the earth's surface, where land is a source of welfare for the community. In the UUPA, the concept of land rights is differentiated into two, namely, first, the right to control of the State as regulated in article 2 which is based on the elaboration of Article 33 of the 1945 Constitution of the Republic of Indonesia. This study aims to determine the process of resolving forestry land disputes at the Land Office of Badung Regency. The research method used is the normative method, namely examining the decision of the head of the BPN RI regional office with the applicable law. The results of the analysis show that based on the Law of the Republic of Indonesia Number 18 of 2003 concerning the prevention and eradication of forest destruction, it is concluded that the causes of the dispute are 6. Based on the Perkab BPN No. 3/2011 there are two land dispute resolution through litigation, namely dispute resolution through court channels, and non-litigation, namely dispute resolution through BPN mediation. Through research, it is hoped that the government can determine the spatial layout of the area so that a single map is created and there are no overlapping policies between the Ministry of Forestry and the Forestry Service